Functional traits as a new approach for interpreting testate amoeba palaeo-records in peatlands and assessing the causes and consequences of past changes in species composition. (September 2015) - Fournier, Bertrand; Lara, Enrique; Jassey, Vincent EJ; Mitchell, Edward AD
Subfossil remains of various groups of organisms preserved in peat and sediment archives are commonly used to infer past environmental changes using transfer functions based on species composition. However, the changes in community structure can also be explored using the functional trait approach. Investigation of functional traits in palaeoecological records can inform about the mechanisms through which abiotic variables such as temperature or moisture impact communities. Moreover, changes in functional traits provide information about changes in ecosystem functioning and can potentially lead to the reconstruction of past processes at the ecosystem scale. Here, we use five key functional traits of arcellinid testate amoebae (TAs), a group of protozoa that are key actors in the microbial foodwebs in peatlands. We apply this approach to the subfossil TA Holocene record of four geographically independent peatlands from Alaska, Switzerland, Poland and Russia. We found that species with larger shells were frequently eliminated from the communities most likely as a result of a switch towards drier conditions. However, when conditions were wetter, species with large shells and species with small shells could coexist because they differed in their trophic niche (i.e. preys). Our results show direct but site-specific links between TA trait data and the depth to water table and pH data inferred from TA species composition. This suggests that past environmental changes influenced both species composition and community function in these ecosystems. Overall, this study demonstrates that species- and trait-based approaches yield complementary information on past environmental changes. For instance, while taxonomic approaches reveal the changes in community composition over time, investigation of traits informs both on the causes and the consequences of these changes on ecosystem functioning.